2013
DOI: 10.2355/isijinternational.53.1953
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Depth Analysis of Corroded Paint-Coated Steel by Confocal Micro-XRF Method

Abstract: A confocal micro-XRF method combined with two individual polycapillary lenses was applied to steel sheets coated with anti-corrosive paint in order to nondestructively observe 3D elemental distribution of paint steels and corroded paint-coated steels. Nondestructive depth analysis and 3D elemental mapping of the painted steel sheets were demonstrated under the confocal XRF configuration. Three different painted steel sheets were prepared by cation electrodeposition coating for automotive onto flat steel sheets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…The authors were able to image the two main layers of the circuitry and the ability to make 2D and 3D investigations on the same sample in the same instrument were particularly valuable and impressive. The same set-up was also used to perform depth proling of corroded painted steel samples 24 and the results demonstrated how effective was the confocal EDXRF technique for non-destructive failure analysis without the need for any sample preparation or sectioning. An interesting application of a confocal EDXRF system was described 25 for the in situ measurement of ion distribution close to the electrode surface during electrolysis of a CuCl 2 solution, opening up the possibility for spatially-resolved analysis of mass transfer in electrolytic tanks, perhaps even with some degree of temporal resolution.…”
Section: Laboratory Instruments and Excitation Sourcesmentioning
confidence: 99%
“…The authors were able to image the two main layers of the circuitry and the ability to make 2D and 3D investigations on the same sample in the same instrument were particularly valuable and impressive. The same set-up was also used to perform depth proling of corroded painted steel samples 24 and the results demonstrated how effective was the confocal EDXRF technique for non-destructive failure analysis without the need for any sample preparation or sectioning. An interesting application of a confocal EDXRF system was described 25 for the in situ measurement of ion distribution close to the electrode surface during electrolysis of a CuCl 2 solution, opening up the possibility for spatially-resolved analysis of mass transfer in electrolytic tanks, perhaps even with some degree of temporal resolution.…”
Section: Laboratory Instruments and Excitation Sourcesmentioning
confidence: 99%
“…Therefore, the method was used in the study of layer structures, such as paintings [106][107][108][109][110][111][112][113][114][115][116] and arts and crafts [117][118][119], multilayer semiconductor devices [120]. The method can be used to study mechanism parts [121], corrosion of metals [122,123], in operando energy converters [124,125], interfaces " liquid/solid" [126]. The possibility of using the CXFS method in medicine [127][128][129], geology [130][131][132], archeology [133][134][135], criminology [136,137], study of printed goods [138], environmental studies [139], studies of near-Earth space and outer space [140] is shown, as well as in pharmaceuticals since the mapping of various complexes in a tablet is an important problem for manufacturing quality control, as well as to detect counterfeits.…”
Section: Confocal X-ray Opticsmentioning
confidence: 99%
“…Поэтому метод использовался при изучении слоистых структур, таких как произведения живописи [106][107][108][109][110][111][112][113][114][115][116] и прикладного искусства [117][118][119], многослойные полупроводниковые устройства [120]. Метод может применяться для изучения деталей механизмов [121], коррозии металлов [122,123], in operando преобразователей энергии [124,125], границ раздела " жидкость/твердое тело" [126]. Показана возможность использования метода КРФС в медицине [127][128][129], геологии [130][131][132], археологии [133][134][135], криминалистике [136,137], изучении печатной продукции [138], исследовании окружающей среды [139], околоземного пространства и космоса [140], а также в фармацевтике, поскольку картирование различных комплексов в таблетке является важной проблемой для производственного контроля качества, а также для обнаружения подделок.…”
Section: конфокальная рентгеновская оптикаunclassified